Efficacy of autologous platelet rich plasma over conventional mechanical fixation methods in split thickness skin grafting - Thimmanahalli, Girish Umashankar; Kumar, Mahesh (International Surgery Journal, 2018)
Background: Platelet-Rich Plasma (PRP) is an autologous product derived from whole blood through the process of gradient density centrifugation. After skin graft reconstruction, the healing process is longer and may be difficult, depending on the wound site, skin defect size, and patient comorbidities. The potential value of PRP lies in its ability to incorporate high concentrations of platelet-derived growth factors into the skin graft. Since not all patients afford commercially available recombinant platelet rich plasma for skin graft, platelet extract from patient’s own blood is being used in this study to test and demonstrate the therapeutic role of PRP in skin graft. The aim of this randomized, prospective study is to compare the effectiveness of PRP in skin graft with conventional method like sutures, staplers or glue. Methods: The source of data were the patients admitted as inpatients for the management of wounds to the department of general surgery, JSS Hospital, Mysore from September 2016 to September 2018. Total of 60 patients were studied; 30 cases were randomly chosen for study with autologous platelet rich plasma and 30 cases received conventional methods like staples/sutures used to anchor the skin grafts in a control group. Results: Autologous PRP showed faster and better healing rates. With PRP study group instant graft adherence was seen in all cases. Hematoma, graft edema, discharge from graft site, frequency of dressings and duration of stay in hospital were significantly less in the PRP. There were no adverse effects or reactions seen with the use of autologous PRP among the study group. Conclusions: The combination of PRP with Split Thickness Skin Graft (STSG) significantly improved clinical outcomes and shortened the wound healing time. Therefore, this treatment combination could provide a way to heal skin after skin graft reconstruction with minimal recovery time. It is found to be highly beneficial in many aspects both to the patient and surgeon based on our results.